Role of serum progesterone in threatened miscarriage - Dave, Anupama; Patil, Ranjana; Bansal, Priya; Malhotra, Anjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Miscarriage is the inadvertent loss of a pregnancy before the fetus is viable. The World Health Organization defines this un-survivable state as an embryo or fetus weighing 500 grams or less, which typically corresponds to a fetal age (gestational age) of 20 to 22 weeks or less. Methods: The present study was conducted in the Department of Obstetrics and Gynaecology, M. G. M. Medical College and M.Y. Hospital, Indore from October 2013 to October 2014 on 100 patients. Results: The incidence of first trimester threatened miscarriage, in the Gynaec O.P.D. of M.Y. Hospital, Indore, was 8.8%. The most common risk factor was a history of previous miscarriages in 38% of cases while 9% had advanced maternal age and 35% had advanced paternal age. History of preterm labour was positive in 25% cases and that of congenital anomaly in previous pregnancy in 7% cases. UTI and vaginitis were diagnosed in 10% and 11% cases respectively. Systemic illness was in 24% cases while 6% cases had endocrine disorders. On USG missed miscarriage was found in 8% inconclusive ultrasound was found in 34% cases, rest were normal. Of the 38 cases giving history of previous 1, 2, 3 and more than or equal to 4 miscarriages were 22%, 6%, 8% and 2 % respectively. 36% of the patients presented with bleeding per vaginum. only while 30% had bleeding with pain and 33% cases had only pain in abdomen. On USG 58% had normal scans. USG scan was inconclusive in 34% and only 35% continued with viable pregnancy, rest aborted. 7 of the 100 cases had preterm labour and 51 cases continued to term. Rest 42 aborted. H/o contact, travel, trauma, heavy work did not have any statistically proven effect on outcome of pregnancy. Conclusions: Progesterone assays are currently available in most immunoassay platforms and have shown excellent performance in terms of assay sensitivity, specificity, accuracy and precision with rapid turnaround times. Furthermore, the cost per test for progesterone assay is affordable. Several studies have shown that progesterone is the most specific biomarker for distinguishing viable from nonviable pregnancies. The downfall of progesterone as a biomarker is due to the different cut-off values used by researchers. The cut-off values were also determined on different study populations.